Egypt 1:100,000. (GSGS (Series) ;)
Sheet numbers and titles : 29/32. [Suez, town and entry to the Canal, in Arabic] ; 32/54. El Mahareq (El Khargo Oasis) ; 92/72. Port Said, 1944 + a blueprint copy of the 1941 edition.